Degree of Practice of Teachers of Gifted Students of Distance Education during Corona Pandemic (Covid-19) at King Abdullah II School of Excellence in Salt - Al Shibly , Ra'fat Abd Al Fatah Ibraheem; Alramamneh , Abdel Latif Khalaf Suleiman; Sabayleh, Obaid Abdelkarim Obaid (Dirasat: Educational Sciences, 2022)
Objectives: The study aims to identify the degree to which teachers of gifted students practice distance learning during Coronavirus pandemic (Covid-19) at King Abdullah II School for Excellence in the city of Salt from teachers' point of view. Methods: In order to achieve the objectives of the study, a questionnaire consisting of 27 paragraphs was developed. The indications of validity and reliability of the questionnaire were ascertained. The questionnaire was distributed online to (22) male and (18) female teachers from King Abdullah II Schools for Excellence in the city of Salt. Results: The results showed that the degree to which teachers of gifted students practice distance education during the Coronavirus pandemic from the teachers' point of view in King Abdullah II Schools for Excellence in the city of Salt came with a medium level with an arithmetic average of (3.40). The results also indicate that there are no statistically significant differences in the estimates due to gender or academic qualification. The results of the study show that there are no statistically significant differences in the study sample estimates for distance learning services due to experience. Conclusion: The study recommends that the Ministry of Education should follow intensive training strategies for teachers of gifted students. Such training would enhance teachers' abilities to apply distance learning (DL) tools.